Testing for EMC compliance approaches and techniques - Montrose, Mark I. (IEEE Press/Wiley-Interscience, 2004)
The Keep It Simple (KISS) philosophy is the primary focus of this book. It is written in very simple language with minimal math, as a compilation of helpful EMI troubleshooting hints. Its light-hearted tone is at odds with the extreme seriousness of most engineering reference works that become boring after a few pages.